HISTORICAL EMPATHY; THE OPPORTUNITIES, REALITY, AND CHALLENGES OF ONLINE HISTORY LEARNING IN SENIOR HIGH SCHOOL - Labibatussolihah, Labibatussolihah; Adriani, Nour Muhammad; Fathiraini, Nurdiani; Sumirat, Yaya (Nurul Jadid University, 2022)
After two years of online learning, an evaluation is needed to assess whether the changes and adaptations in the process could achieve its objectives. Some adaptations had been done at UPI Laboratory School/s but no study has been conducted to assess its practice and success. Using the sequential exploratory mixed-method with the CIPP Stufflebeam model as a research framework, three teachers and 112 students from two UPI Laboratory Senior High Schools participated in this project. In-depth interviews were conducted with teachers, while online questionnaires were independently developed, validated, and distributed to students. It can be concluded that historical empathy in online learning at UPI Laboratory School/s; 1) is contextually appropriate to the conditions, resources, and needs of the institution and teachers but only part of the participants or students; 2) For Input section, aspects of the ability and capacity of teachers need to be improved; 3) As Process section, the teacher's workload and time constraints are the obstacles faced, and 4) in the Product section, the level of satisfaction among the participants varies with the theoretical aspects, dominating the practical outcomes of historical empathy-based learning. Overall, the learning program fulfilled the merit of being retained with some basic improvements.